Individual Participant Data (IPD) Meta-analyses of Randomised Controlled Trials: Guidance on Their Use. - Jayne F Tierney (PLoS Medicine, 2015)
Jayne Tierney and colleagues offer guidance on how to spot a well-designed and well-conducted individual participant data meta-analysis.